KONSEP KURIKULUM TERINTEGRASI: Analisis Kurikulum Formal dengan Pesantren - Ahmad Budiyono (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2021)
The global world really needs the development of IMTAQ is very important, because without being framed by faith and piety, the competence of science and technology will be less meaningful for the life of the nation, it is even feared that it will be wild and uncontrolled, which will manifest in the erosion of moral values. Therefore the pesantren and formal school curricula need to be framed in the form of integration. Only the integration of the curriculum can connect the two education (Pesantren and formal education). The integrated curriculum (Integrated Curriculum) is an attempt to integrate learning materials from various kinds of lessons. Integration is created by focusing lessons on specific problems that require solutions with material or materials from various disciplines or subjects. Overall the pesantren curriculum is flexible, in the sense that each student has the opportunity to compile his or her own curriculum completely or partially according to their needs and abilities. Even in pesantren that already have a school education system